Organizational Culture Adaptation as a Mediation Effect of Human Resource Flexibility on Job Satisfaction and its Impact on Employee Performance - Sabuhari, Rahmat (JDM (Jurnal Dinamika Manajemen), 2021)
This research aims to study and analyze the direct effect of human resource flexibility, organizational culture adaptation, and job satisfaction on employee performance. This research also examines the indirect effect of human resource flexibility on employee performance with organizational culture adaptation as a mediating variable; the influence of organizational culture adaptation on employee performance with job satisfaction as a mediating variable; and also the influence of human resource flexibility on job satisfaction with organizational culture adaptation as a mediating variable. The sample in this study amounted to 153 employees of Courier Service Companies. The sampling technique uses sampling with certain criteria. SEM-PLS is used to test the hypothesis. The results showed that the human resources flexibility and job satisfaction had a significant influence on employee performance, but organizational culture adaptation did not have a significant effect on employee performance, this also resulted in the adaptation of organizational culture not able to mediate the effect of human resource flexibility on employee performance. However, the adaptation of organizational culture is able to mediate the effect of human resource flexibility on job satisfaction. Job satisfaction is also able to mediate the influence of organizational culture adaptation on employee performance.